Gen Z and Millennials' Creative Solutions for Integrated Marketing Communication for Ancol Gondola Amusement Rides in 2025 - Bima Petala Rifardhi; Rosmawaty Hilderiah Pandjaitan; Afdal Makkuraga Putra (International Journal Labs, 2025)
The Ancol Gondola is a cable car entertainment ride at Taman Impian Jaya Ancol, but since 2021 there has been a decrease in the number of visitors. According to data from the General Election Commission (KPU) in 2024, currently the number of Gen Millennials in Indonesia is around 66 million people (33.60%) and Gen Z is around 44 million people (22.85%). Therefore, it is important for Gondola Ancol to know what and how Gen Z and Millennial creative solutions for integrated marketing communication for Gondola Ancol in 2025. The purpose and purpose is, to uncover and explain, as well as find